P0704PROTECTIVE EFFECT OF DUAL ACTING LIGAND TARGETING A2A AND A3 ADENOSINE RECEPTOR ON OBSTRUCTION-INDUCED KIDNEY INJURY IN MICE. (6th June 2020) - Pak, Eun Seon; Lee, Jiyoun; Ha, Hunjoo
Abstract: Background and Aims: Chronic kidney disease (CKD) has been a worldwide public health problem, and the current therapeutic strategies against CKD are limited. Adenosine plays a significant role in protection against cellular damage in the regions with high metabolism. All 4 known subtypes of adenosine receptors such as A1 AR, A2A AR, A2B AR, and A3 AR are expressed in the kidney. While A2A AR agonists protect the kidney against inflammation, our previous study has demonstrated that an A3 AR regulator effectively prevented diabetic kidney injury. The present study examined the preventive effect of LJ-4459, a newly synthesized dual acting ligand targeting A2A AR and A3 AR, on unilateral ureteral obstruction (UUO)-induced kidney injury in mice. Method: UUO surgery was performed in 6-week-old male C57BL/6 mice. LJ-4459 was administered by oral gavage at dose of either 1 or 10 mg/kg per day. The control group was administered an equal volume of vehicle (0.25% carboxymethyl cellulose). Results: LJ-4459 effectively prevented tubular damage presented by significantly reduced NGAL expression and tubular necrosis in the obstructed kidney. LJ-4459 effectively inhibited elevation of a-SMA, collagen I, and collagen IV protein expression as well as picro sirius red staining in the obstructed kidney, suggesting antifibrotic effect of LJ-4459. LJ-4459 also inhibited inflammation as estimated by significantly reduced F4/80 positive-stained area and protein expression of p-NF-kB and ICAM1. Conclusion: The results suggest that LJ-4459 may become a potential therapeutic agent against interstitial fibrosis, a common feature of CKD.